APLIKASI PENGUBAH BENTUK NORMAL CHOMSKY MENJADI BENTUK NORMAL GREIBACH DENGAN METODE SUBSTITUSI - Rico Andrian; Wamiliana .; Andikha Yunar Cornelius Dabukke (Jurnal Komputasi, 2015)
The research was conducted with making an application to change Chomsky Normal Form (CNF) to Greibach Normal Form (GNF) with substitution method. One way of representing Context Free Grammar (CFG) is using Greibach Normal Form (GNF). The development of the application starts by making algorithm with prototype method to change Chomksy Normal Form (CNF) to Greibach Normal Form (GNF). This application is used to change Chomsky Normal Form to Greibach Normal Form and the results show that the application can change Chomsky Normal Form to Greibach Normal Form smoothly.The input for the application must be on Chomksy Normal Form (CNF).Â Keywords: Chomsky Normal Form, Context Free Grammar, Greibach Normal Form, Prototype MethodÂ